Quality Predictability and the Welfare Benefits from New Products: Evidence from the Digitization of Recorded Music - Luis Aguiar; Joel Waldfogel (European Commission, Joint Research Centre (JRC), 2015)
We explore the consequence of quality unpredictability for the welfare benefit of new products, using recent developments in recorded music as our context. Digitization has expanded consumption opportunities by giving consumers access to the "long tail" of existing products, rather than simply the popular products that a retailer might stock with limited shelf space. While this is clearly beneficial to consumers, the benefits are somewhat limited: given the substitutability among differentiated products, the incremental benefit of obscure products - even lots of them - can be small. But digitization has also reduced the cost of bringing new products to market, giving rise to a different sort of long tail, in production. If the appeal of new products is unpredictable at the time of investment, as is the case for cultural products as well as many others, then creating new products can have substantial welfare benefits. Technological change in the recorded music industry tripled the number of new products between 2000 and 2008. We quantify the effects of new music on welfare using an explicit structural model of demand and entry with potentially unpredictable product quality. Based on plausible forecasting models of expected appeal, a tripling of the choice set according to expected quality adds more than fifteen times as much consumer surplus as the usual long-tail benefits from a tripling of the choice set according to realized quality.
Keywords: D60; L13; L82; O33; 330; music; Welfare; Entry; Digitization; Recorded Music